The Hidden Dimension of Happy Cultural Cooperation - Sauvage, Emmanuelle (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2018)
Cross-cultural management research usually postulates that mutual expectations must be clearly assessed and that it is necessary for people from different cultural areas to share a common vision in order to efficiently collaborate. This research examines the link between intercultural understanding and relational efficiency by studying a “happy” and successful Franco-Latino-American case. It challenges the above-mentioned postulate and reveals that relational efficiency relies upon compatible positive understandings of a same situation rather than upon similar understandings, hence the notion of productive misunderstandings.